Characterization and Modulation of Systemic Inflammatory Response to Exhaustive Exercise in Relation to Oxidative Stress - Katsuhiko Suzuki; Takaki Tominaga; Ruheea Taskin Ruhee; Sihui Ma (MDPI AG, 2020)
Exhaustive exercise induces systemic inflammatory responses, which are associated with exercise-induced tissue/organ damage, but the sources and triggers are not fully understood. Herein, the basics of inflammatory mediator cytokines and research findings on the effects of exercise on systemic inflammation are introduced. Subsequently, the association between inflammatory responses and tissue damage is examined in exercised and overloaded skeletal muscle and other internal organs. Furthermore, an overview of the interactions between oxidative stress and inflammatory mediator cytokines is provided. Particularly, the transcriptional regulation of redox signaling and pro-inflammatory cytokines is described, as the activation of the master regulatory factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is involved directly or indirectly in controlling pro-inflammatory genes and antioxidant enzymes expression, whilst nuclear factor-kappa B (NF-κB) regulates the pro-inflammatory gene expression. Additionally, preventive countermeasures against the pathogenesis along with the possibility of interventions such as direct and indirect antioxidants and anti-inflammatory agents are described. The aim of this review is to give an overview of studies on the systematic inflammatory responses to exercise, including our own group as well as others. Moreover, the challenges and future directions in understanding the role of exercise and functional foods in relation to inflammation and oxidative stress are discussed.